Genetic Variants and Drug Efficacy in Tuberculosis: A Step toward Personalized Therapy - Khan, Almas; Abbas, Mohammad; Verma, Sushma; Verma, Shrikant; Rizvi, Aliya Abbas; Haider, Fareya; Raza, Syed Tasleem; Mahdi, Farzana (Global Medical Genetics, 2022)
Tuberculosis (TB) continues to be a major infectious disease affecting individuals worldwide. Current TB treatment strategy recommends the standard short-course chemotherapy regimen containing first-line drug, i.e., isoniazid, rifampicin, pyrazinamide, and ethambutol to treat patients suffering from drug-susceptible TB. Although Mycobacterium tuberculosis, the causing agent, is susceptible to drugs, some patients do not respond to the treatment or treatment may result in serious adverse reactions. Many studies revealed that anti-TB drug-related toxicity is associated with genetic variations, and these variations may also influence attaining maximum drug concentration. Thus, inter-individual diversities play a characteristic role by influencing the genes involved in drug metabolism pathways. The development of pharmacogenomics could bring a revolution in the field of treatment, and the understanding of germline variants may give rise to optimized targeted treatments and refine the response to standard therapy. In this review, we briefly introduced the field of pharmacogenomics with the evolution in genetics and discussed the pharmacogenetic impact of genetic variations on genes involved in the activities, such as anti-TB drug transportation, metabolism, and gene regulation.
Keywords: mycobacterium tuberculosis; germline variants; anti-TB drug-related toxicity; pharmacogenomics; personalized medicine